English Language - Febriyanto; Regania Pasca Rassy; Halil Akhyar; Muhammad Iqbal Raissilki (Journal of Computer Science and Informatics Engineering (J-Cosine), 2025)
The rapid development of immersive technology, particularly Augmented Reality (AR), has significantly supported the digitization of infrastructure in the Fourth Industrial Revolution. In the property industry, conventional visualization media such as two-dimensional (2D) floor plans are often difficult for non-technical users to interpret. This study develops an Android-based application, AR Site Visualization, that converts 2D floor plans into interactive three-dimensional (3D) models in real time. The development applied the Multimedia Development Life Cycle (MDLC) framework with six stages, employing Unity, Vuforia SDK, and Lean Touch for feature integration. The 3D models were created using SketchUp and Enscape to ensure realistic visualization. Evaluation through Black Box Testing and formative assessments demonstrated that all features, including marker scanning, 3D visualization, rotation, zoom, and translation, worked effectively, achieving a feasibility score of 71.5%. The results indicate that AR Site Visualization enhances spatial understanding and improves design communication users.